2019
DOI: 10.1101/619775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating patterns of thermal tolerance and phenotypic plasticity with population genetics to improve understanding of vulnerability to warming in a widespread copepod

Abstract: 8Differences in population vulnerability to warming are defined by spatial patterns in thermal 9 adaptation. These patterns may be driven by natural selection over spatial environmental 10 gradients, but can also be shaped by gene flow, especially in marine taxa with high dispersal 11 potential. Understanding and predicting organismal responses to warming requires disentangling 12 the opposing effects of selection and gene flow. We begin by documenting genetic divergence of 13 thermal tolerance and development… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 127 publications
4
34
0
Order By: Relevance
“…They show the presence of four major clades. This is in agreement with our observations where the four corresponding clades would presumably be clades III (S), V, VI (X), and VII (F), note that clade IV in our study is only found in Texas and Brazil, not sampled by Sasaki and Dam (2019). In their study, they analyze their data under the assumption that these clades are the same species and treat their samples from each location as a population.…”
Section: Acartia Tonsa Species Complexsupporting
confidence: 92%
See 4 more Smart Citations
“…They show the presence of four major clades. This is in agreement with our observations where the four corresponding clades would presumably be clades III (S), V, VI (X), and VII (F), note that clade IV in our study is only found in Texas and Brazil, not sampled by Sasaki and Dam (2019). In their study, they analyze their data under the assumption that these clades are the same species and treat their samples from each location as a population.…”
Section: Acartia Tonsa Species Complexsupporting
confidence: 92%
“…Making such distinctions are essential before undertaking any population-specific study on A. tonsa. For example, a recent study by Sasaki and Dam (2019) investigated patterns of thermal tolerance and phenotypic plasticity in A. tonsa. They collected specimens of A. tonsa from the Northwest Atlantic (north of 40°N) and Florida (south of 30°N) including coasts in the Atlantic and the Gulf of Mexico.…”
Section: Acartia Tonsa Species Complexmentioning
confidence: 99%
See 3 more Smart Citations